Adherence to Physical Rehabilitation in Patients With Delirium Post Neurosurgery: A Study Protocol - Júlio Belo Fernandes; Leonor Monteiro; Cristina Rodrigues; Marlene Monteiro; Ana Gonçalves; Mónica Pinto; Sónia Fernandes; Ana Romão; Josefa Domingos; Catarina Godinho (International Journal of Qualitative Methods)
Delirium is an acute neurocognitive disorder characterized by confusion, disorientation, and fluctuating levels of arousal. It is commonly observed in patients following neurosurgery. This condition can lead to various adverse outcomes, including cognitive and functional decline, prolonged hospital stays, and increased mortality rates. Physical rehabilitation is crucial for these patients’ recovery, as it promotes functional improvement, reducing long-term disability risks, and enhancing overall quality of life. While evidence supports rehabilitation’s value in delirium management, there is limited understanding of specific strategies to improve adherence to rehabilitation among post-neurosurgery patients experiencing delirium. This study explores the rehabilitation workforce’s perspectives on strategies to enhance adherence to physical rehabilitation in neurosurgery patients with delirium. This study will use a qualitative, descriptive exploratory design to investigate strategies that support adherence to rehabilitation. We will use purposive sampling to recruit a diverse group of rehabilitation professionals, including nurses, physiatrists, physiotherapists, speech and language therapists, and occupational therapists, from Lisbon, Portugal. Data will be collected through semi-structured interviews guided by an interview script and analyzed using thematic analysis. Demographic data will be processed with SPSS software, while QDA Miner Lite will assist with coding and qualitative analysis. Identifying effective strategies to promote adherence to rehabilitation in neurosurgery patients affected by delirium could improve patient recovery, reduce healthcare burdens, and inform evidence-based guidelines. The findings of this study may provide practical insights for healthcare providers, administrators, and policymakers, ultimately supporting higher-quality care for this patient population.